Climate Change and the Politics of Apocalyptic Redirection. (May 2023) - Cross, Ben
Alison McQueen's study of the historical role of apocalyptic ideas in realist political theory cautiously proposes the 'redirection' of apocalyptic thought as a plausible alternative to its rejection. Apocalyptic redirection, so understood, uses apocalyptic language to describe potential future catastrophes in order to inspire drastic action to prevent them. Although McQueen acknowledges that apocalyptic redirection may have certain risks, she suggests it may be an appropriate response to the crisis of climate change. In this article, I aim to show that this use of the discourse of apocalyptic redirection is ideologically problematic. I argue that it involves conflating the interests of those who are at least moderately materially comfortable with the interests of humanity as a whole. I will also draw on the 2019 'Stop Adani Convoy' in Australia as a case study to show how the ideological character of this discourse renders it ill-suited to generating popular support for action on climate change, and liable to reproduce existing power relations.